Матеріали з рукописної збірки Д. І. Яворницького "Український простолюд в його творчості" (Народна творчість та етнографія, 2005)
Dmytro Yavomytskyj letters to V. Kravchenko (1862 - 1945), M. Serhijev (1904 - 1945) - a regional ethnologist, school teacher in the village Tomakivka, Dnipropetrovsk region - are presented to the readers' attention; as well as folk legends from a manuscript collection of narrative folklore "Ukrainian People in Their Creative Activities" recorded by D. Yavomytskyj: all from the National archival scientific funds of manuscripts and phonorecords of the Institute of Art Studies, Folklore and Ethnology, National Academy of Sciences.